2014
DOI: 10.5455/ijmsph.2013.061120132
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression in diabetic Patients

Abstract: Background: Diabetes mortality is increased when accompanied with depression. Screening for depression is recommended by national and international authorities. Aims & Objective:To have an estimate of the diabetic patients at risk of depression and to identify the risk factors for depression in diabetic patients. Material and Methods:The study was designed as a cross-section design. Two hundred and three patients were selected by convenience sample. Diabetic patients of either sex, 18 years and older, new to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…26 In Riyadh, AL-Baik et al (2013) reported a prevalence of 45.8%. 27 In Makkah (2010), the prevalence was 41.9%. 28 In the Qatif area, a prevalence of 14.5% for depression among diabetic has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…26 In Riyadh, AL-Baik et al (2013) reported a prevalence of 45.8%. 27 In Makkah (2010), the prevalence was 41.9%. 28 In the Qatif area, a prevalence of 14.5% for depression among diabetic has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] this finding goes in concordance with a large meta-analyses of prevalence of depression in adults with diabetes by Anderson et al 27 which included 42 studies that found prevalence of depression in clinical samples is 32.7%, decreases by using structured interviews to 14.2%, and increases by using selfreport instruments up to 34.9%, and earlier study by Gavard et al 28 which found that major depression was present in 14.7%, and elevated depression symptoms in 26% of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 In Riyadh, AL-Baik et al (2013) reported a prevalence of 45.8%. (21) In the Qatif area, a prevalence of 14.5% for depression among diabetic has been reported. 22 In Jeddah (2005), it was 48%.…”
Section: Discussionmentioning
confidence: 99%